"Flash" synthesis of "giant" Mn-doped CdS/ZnS nanocrystals for high photostability. Issue 108 (20th October 2015) - Xu, Ruilin; Liao, Chen; Zhang, Huichao; Huang, Bo; Fan, Kai; Gao, Xiaoqin; Cui, Yiping; Zhang, Jiayu
Abstract : "Flash" synthesis of "giant" Mn-doped CdS/ZnS nanocrystals with high photostability is developed for the application in white LEDs. Abstract : Colloidal semiconductor nanocrystals (NCs) could exhibit good photostability if a thick shell (usually more than 10 monolayers (MLs)) with wide bandgap is epitaxially grown onto them. But the photoluminescence (PL) quantum yield (QY) of this kind of "giant" NCs is significantly reduced by the accumulation of non-radiative defects during the rapid growth of thick shell. By optimizing the ratio of ligands and the concentration of precursors, we developed a lower-temperature (L-T) "flash" synthesis method to prepare giant Mn-doped CdS/ZnS core/shell NCs. The thick ZnS shell was overcoated at the injection- and growth-temperature of 340 and 315 °C respectively, and ZnS shell with thickness up to 18 MLs could be grown within only 9 min. Because of the suppressed diffusion of Mn 2+ dopants and the accompanying limited alloying forming, the energy transfer from the photoexcited exciton in NCs' core towards Mn 2+ dopants remains rapid, resulting in the increase of PL-QY from 25% (typical "flash") to 36% (L-T "flash") for the doped NCs with 14 ML ZnS-shell, much higher than the undoped "flash" CdS/ZnS (13 MLs) NCs' PL-QY of less than 1%. Compared with PMMA-coated thin-shell NCs with the continuing PL degradation, PMMA-coated giant ZnS-shell NCs exhibit the high photostability, throwing light on the application of "flash" giant ZnS-shell NCs for displays and lighting. The high-photostable "flash" giant Mn-doped NCs, with broad band emission and big redshifted emission peak position of ∼620 nm, are used as color converters in white light-emitting diodes with a color rendering index of 80, color coordinates of (0.34, 0.38), and a correlated color temperature of 5397 K.